Preparing Students for Inclusive Education Through Effective Organization of Educational Work in Specialized State Educational Institutions (Diversity Research: Journal of Analysis and Trends, 2023)
the article talks about methods of preparing students for inclusive education through effective organization of educational work in specialized state educational institutions